Habsburg Austria: Experiments in Non-Territorial Autonomy. Issue 1 (1st January 2016) - Kuzmany, Börries
Abstract: In the early twentieth century, three provinces of the Austrian half of the Habsburg Empire enacted national compromises in their legislation that had elements of non-territorial autonomy provisions. Czech and German politicians in Moravia reached an agreement in 1905. In the heavily mixed Bukovina, Romanian, Ukrainian, German, Jewish and Polish representatives agreed on a new provincial constitution in 1909. Last but not least, Polish and Ukrainian nationalists compromised in spring 1914, just a few months before the outbreak of the First World War vitiated the new provisions. Even though the provisions of these agreements varied substantially, new electoral laws introducing national registers were at their heart. These were designed to ensure a fairer representation of national groups in the provincial assemblies and to keep national agitation out of electoral campaigns. The earliest compromise in Moravia went furthest in consociational power sharing. However, the national bodies within the provincial assembly had no right to tax their respective national communities, and the provisions of the provincial constitutions kept the non-nationally defined nobility as an important counterbalance. The compromises in Bukovina and Galicia, even if they categorised all inhabitants nationally, contented themselves with even less autonomous agency for the national bodies in the provincial assemblies and rather emphasised the symbolic elements of national autonomy. The non-territorial approach in all three crownlands, however, was an instrument to reorganise multi-ethnic provinces that increasingly became the model for national compromises in other Austrian provinces.